ENGLISH FOR ACADEMIC PURPOSES COURSE FOR TERTIARY EDUCATION STUDENTS: A NEED ANALYSIS - Marham Jupri Hadi (The Center for Language Development, Mataram State Islamic University., 2016)
Abstract: This article presents need analysis as the outset for designing an English for Academic Purposes for participants learning in English Language Education of a private owned university in West Nusa Tenggara. The course was intended as a bridging program to enhance participants’ ability to use academic English for a variety of puposes in particular to accomplish their assignments throughout their study. However, further analysis was carried out to gain deeper understanding about the participants learning needs through only survey, questionnaires and discussion with lecturers. This article further describes the rationale for conducting a need analysis, participans, and the steps of doing need analysis